Enterprise Architecture Zachman Framework Mapping of SIAKAD Jambi University to Support Digital Academic Services in Higher Education - Dzaky, Dedi Imaduddin; Zurweni, Zurweni; Sofyan, Sofyan (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
This study aims to analyze the alignment of the academic information system at Jambi University (UNJA) using the Zachman Framework and to examine the Enterprise Maturity Level in the implementation of Enterprise Architecture within the Academic Information System (SIAKAD) of Jambi University. The study applies Enterprise Architecture Planning (EAP) as a reference method for developing information architecture. EAP is oriented toward business needs and consists of data architecture, application architecture, technology architecture, and an implementation plan. In addition, the Zachman Framework is used to assess alignment from three enterprise architecture functions: context, concept, and construction. The value chain profile of the academic information system business process is also identified and analyzed. The study found a value chain profile within the business processes of Jambi University’s Academic Information System (SIAKAD). The mapping results based on the Zachman Framework reveal the condition of each business component and provide a basis for evaluating the maturity level of Enterprise Architecture implementation in the system. This study provides recommendations for the future development of each business component of Jambi University’s Academic Information System based on the Zachman Framework. The findings contribute to improving the alignment of information systems with business needs and support the achievement of the university’s mission through better enterprise architecture planning.